PRACTICAL STRATEGIES TO BUILD CONFIDENCE IN SPEAKING ARABIC - Devi, Mira; Taufik Taufik (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Speaking skills are productive language abilities to express thoughts, ideas and feelings verbally. The aim of this research is to develop and present practical strategies that can build courage in speaking Arabic with confidence. This research uses a library study method by collecting several relevant reference sources and then analyzing and compiling them systematically so that readers can easily digest and understand the contents of the article. The results obtained from the research are several ways or strategies to grow courage in speaking Arabic, such as overcoming fear and doubt, building a strong basic foundation, practicing every day, not being afraid to make mistakes, utilizing existing technology, and applying appropriate learning methods. varies.